1997
DOI: 10.1046/j.1440-169x.1997.t01-5-00008.x
|View full text |Cite
|
Sign up to set email alerts
|

A planarian orthopedia homolog is specifically expressed in the branch region of both the mature and regenerating brain

Abstract: To analyze the organization of planarian brain, a homolog of the homeobox-containing gene Orthopedia (Otp) from planarian, Djotp, was isolated. The homeodomain of Djotp differs from mouse Otp by only two amino acids. This conservation extends to include a 12 amino acid motif downstream of the homeodomain. Whole mount in situ hybridization studies indicated that Djotp is specifically expressed in the branch structures of the normal planarian adult brain. During regeneration, Djotp is expressed in the presumptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
198
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 208 publications
(201 citation statements)
references
References 16 publications
2
198
0
1
Order By: Relevance
“…37. Samples were loaded into a BioLane HTI automated in situ hybridization instrument (Hölle & Hüttner, Tübingen, Germany) and processed as described in ref.…”
Section: Whole-mount In Situ Hybridization To Sexual Planariansmentioning
confidence: 99%
“…37. Samples were loaded into a BioLane HTI automated in situ hybridization instrument (Hölle & Hüttner, Tübingen, Germany) and processed as described in ref.…”
Section: Whole-mount In Situ Hybridization To Sexual Planariansmentioning
confidence: 99%
“…The sixth to ninth branches cluster more closely and form auricles on the surface, which may function as the sensory organ of taste. We also found that these structurally distinct diverse domains are defined by the discrete expression of three evolutionarily conserved homeobox genes, DjotxA, DjotxB and Djotp (Umesono et al 1997. Interestingly, expression analysis of these genes via EST projects and DNA microarray hybridization strongly suggests that the expression domains defined by the three homeobox genes may actually correspond to functional domains (figure 2).…”
Section: Structure Of the Planarian Brainmentioning
confidence: 77%
“…For colorimetric whole-mount in situ hybridization (WISH) analyses, animals were processed using an In situ Pro hybridization robot (Abimed/Intavis), as previously described (Molina et al, 2007;Umesono et al, 1997). For fluorescent whole-mount in situ hybridization (FISH), planarians were fixed and stained as previously described (Pearson et al, 2009).…”
Section: Gene Expression Analysismentioning
confidence: 99%